Effect of Malathion on Reproductive Parameters of Engorged Female Rhipicephalus (Boophilus) microplus Ticks of Punjab Districts, India. (15th October 2015) - Jyoti,; Singh, N. K.; Singh, Harkirat; Rath, S. S.
Abstract : The present study was aimed at evaluating effects of malathion on the various reproductive parameters, namely, egg mass weight (EMW), reproductive index (RI), percentage inhibition of oviposition (%IO), and hatchability percentage of eggs of Rhipicephalus ( Boophilus ) microplus (Canestrini 1887) females from 19 districts of Punjab, India. The effect on various parameters was found to be dose dependent and more discernible upon exposure to higher concentrations. Complete cessation of egg laying was recorded in tick isolates on exposure to 5000 ppm and above. The values of %IO ranged in 4.4–68.6, 25.2–76.2, 35.6–100.0, 45.7–100.0, and 71.4–100.0 in groups treated with 1250, 2500, 5000, 10000, and 20000 ppm of malathion, respectively. A low hatching % was recorded in eggs of all treated female ticks in comparison to control treated with distilled water and complete inhibition of hatching was recorded at 10000 ppm and above. However, the survival of the hatched larvae was not affected and was similar to control group. The results of the current study can be of immense help in formulation and implementation of effective tick control measures.